Altered functional networks in long‐term unilateral hearing loss: A connectome analysis. Issue 2 (18th January 2018) - Zhang, Yanyang; Mao, Zhiqi; Feng, Shiyu; Liu, Xinyun; Lan, Lan; Zhang, Jun; Yu, Xinguang
Abstract: Introduction: In neuroimaging studies, long‐term unilateral hearing loss (UHL) is associated with functional changes in specific brain regions and connections; however, little is known regarding alterations in the topological organization of whole‐brain functional networks and whether these alterations are related to hearing behavior in UHL patients. Methods: We acquired resting‐state fMRI data from 21 patients with UHL caused by acoustic neuromas and 21 matched healthy controls. Whole‐brain functional networks were constructed by measuring interregional temporal correlations of 278 brain regions. Alterations in interregional functional connectivity and topological properties (e.g., small‐world, efficiency, and nodal centrality) were identified using graph‐theory analysis. The subjects also completed a battery of hearing behavior measures. Results: Both UHL patients and controls exhibited efficient small‐world properties in their functional networks. Compared with controls, UHL patients showed increased and decreased nodal centrality in distributed brain regions. Furthermore, the brain regions with significantly increased and decreased functional connections associated with UHL were components of the following important networks: (1) visual network; (2) higher‐order functional networks, including the default‐mode and attention networks; and (3) subcortical network and cerebellum. Intriguingly, the changes in intranetwork connections in UHL were significantly correlated with disease duration and hearing level. Conclusions: This study revealed connectome‐level alterations involved in multiple large‐scale networks related to sensory and higher‐level cognitive functions in long‐term UHL patients. These reorganizations of the brain in UHL patients may depend on the stage of deafness and hearing level. Together, our findings provided empirical evidence for understanding the neuroplastic mechanisms underlying hearing impairment, establishing potential biomarkers for monitoring the progression and further treatment effects for UHL patients. Abstract : Connectome‐level alteration involved in sensory and higher‐level cognitive networks was observed in UHL patients. Specific altered intranetwork connections were significantly correlated with clinical measures in UHL patients. Future work might use functional neuroimaging assessments to best formulate a comprehensive clinical treatment plan for UHL patients.